Thermodynamic Modelling of Phenolic Compound Extraction from Bio-Oil Derived from Multi-Feedstock Biomass Pyrolysis - Syauqi, Alifyan; Fardhyanti, Dewi Selvia; Prasetiawan, Haniif (Jurnal Bahan Alam Terbarukan, 2025)
Biomass exhibits substantial potential as a renewable energy source in the form of bio-oil; however, further upgrading is required, including the separation of phenolic compounds through liquid–liquid extraction (LLE). Previous studies on LLE modelling of bio-oil have explored variations in feedstock type, pyrolysis temperature, extraction temperature, solvent selection, and thermodynamic models. This study focuses on thermodynamic modelling of phenol extraction from bio-oil derived from the pyrolysis of mixed biomass using the NRTL, UNIQUAC, and UNIFAC models. The objectives are to evaluate the influence of extraction temperature and to identify the most suitable thermodynamic model for phenol extraction from bio-oil produced by mixed biomass waste pyrolyzed at 500 °C. The results demonstrate that extraction temperature significantly influences the LLE behaviour of phenol extraction from mixed biomass waste bio-oil across all evaluated models. Correlation analysis and root mean square deviation (RMSD) values indicate that the NRTL model provides the best predictive performance, particularly at an extraction temperature of 40 °C. Furthermore, the NRTL model is identified as the most appropriate thermodynamic model for predicting phenol extraction from bio-oil produced by the pyrolysis of mixed biomass waste at 500 °C. This superior performance is attributed to the NRTL model’s capability to accurately represent liquid–liquid equilibrium in both binary and multicomponent systems, especially under dilute conditions, outperforming the UNIQUAC and UNIFAC models.